Structural and magnetic properties of Fe76P5(Si0.3B0.5C0.2)19 amorphous alloy - Lavorato, Gabriel Carlos (2012)
Recently, bulk amorphous alloys were produced in the Fe–B–Si–P–C system with high glass forming ability, excellent magnetic properties and the advantage of containing no expensive glass-forming elements, such as Ga, Y, Cr or Nb, having, therefore, a good perspective of commercial applications. In the present work, the Fe76P5(Si0.3B0.5C0.2)19 amorphous alloy prepared by two quenching techniques has been studied. Amorphous ribbons of about 40 μm thick were obtained by planar-flow casting together with cylinders having 1 and 2 mm diameter produced by copper mold injection casting. All the samples appear fully amorphous after X-ray diffraction analysis. A comprehensive set of thermal data (glass, crystallization, melting and liquidus temperatures) were obtained as well as a description of the melting and solidification processes. Mechanical microhardness tests showed that the samples have a hardness of 9.7 ± 0.3 GPa. Good soft-magnetic properties were obtained, including a high magnetization of 1.44 T and a low coercivity (4.5 A/m for ribbons and 7.5 A/m in the case of 1 mm rod samples, both in as-cast state). Thermomagnetic studies showed a Curie temperature around 665 K and the precipitation of new magnetic phases upon temperatures of 1000 K. Furthermore, the frequency dependence of magnetic losses at a fixed peak induction was studied. The results suggest the occurrence of a fine magnetic domain structure in bulk samples. The good soft magnetic properties of the bulk metallic glass obtained by copper mold casting for this particular Fe-based composition suggests possible applications in transformer cores, inductive sensors and other devices.